New data on the Odonate fauna from Graciosa Island (Azores) - Vieira, Virgílio (2013)
[…]. Currently, four odonate species are known from the Azores archipelago (Valle 1940; Gardner 1959, 1960; Belle 1992; Cordero-Rivera et al. 2005; Lorenzo-Carballa et al. 2009), namely, Anax imperator Leach, 1815 (Aeshnidae), Sympetrum fonscolombii (Selys, 1840) (Libellulidae), Ischnura pumilio (Charpentier, 1825) and Ischnura hastata (Say, 1839) (Coenagrionidae). The first three species belong to the European fauna, whereas the last one is native to the Americas (Belle & van Tol 1990; Lorenzo-Carballa et al. 2009; Weihrauch 2011). In a previous paper we found that all four species were known from all islands except Santa Maria and Graciosa, but we proposed that this was due to a lack of sampling and suggested that it is likely that all four species are present in all of the nine islands (Cordero Rivera et al. 2005). Further sampling confirmed the presence of these four species in Santa Maria Island (Lorenzo-Carballa et al. 2009; Tavares et al. 2010). Very few records of odonates have been published for Graciosa. The first was a female S. fonscolombii observed on July 17, 1938 (Valle 1940). No indication of the relevant locality was given. To our knowledge, only A. imperator and S. fonscolombii species were further recorded for Graciosa (Cordero-Rivera et al. 2005; Lorenzo-Carballa et al. 2009), but again without localities. So, the present contribution deals with new odonate records for this island. Given that I. hastata is of great interest in every island of the archipelago due to its unique parthenogenetic reproduction in all its Azorean localities, the first author made two visits to Graciosa in 2004 and 2007, in order to survey the local odonate fauna.